Intelligent Speed Controller for Four Phase Switched Reluctance Motor - Mahalakshmi, G.; Maladhi, D.; Manochitra, G.; Bhavatharini, T.; Nandhakumar, T. (International Journal of Engineering and Technology, 2018)
This paper examines the performance of Fuzzy logic controller with conventional PI controller speed control of four phase Switched Reluctance motor. Switched Reluctance motor has acquired attentiveness in Adjustable speed drive .Because of its less manufacturing and operating cost, fault tolerant capacity ,and high efficiency ,this motor is gains considerable attention. SRM is anyway somewhat hard to control, due to its nonlinear attributes. The dynamic execution anticipated from a variable speed drive incorporates least torque swell, low consistent state blunder, diminished speed overshoot, adaptation to non-critical failure and lessened speed wavering. Rather than linearizing the plant for particular working condition and afterward outlining a direct controller, a straightforward drive framework has been created. The controlled framework incorporates an inward current loop and external speed loop. Winding current and turn on ,turn off angles are utilized as control factors.Â Â Â